A look at victim experiences of cybercrime in South Africa and whether the current legislative framework is equipped to deal with this issue - Smit, Savannah Tuscany (Department of Public Law, 2024)
Cybercrime has become extremely prevalent in society. It is an indiscriminate form of crime that permeates all levels of society. This is especially true after the COVID-19 pandemic which resulted in individuals becoming increasingly reliant on technology for everyday tasks such as working, shopping and connecting with their loved ones. Cybercriminals have taken advantage of the increased use and reliance on technology and have targeted individuals via various online platforms. Based on data collected through an anonymous online survey, this research examines victims' experiences of cybercrime and the response to this crime, including whether participants were aware of the legal remedies available to them and how to report that they had been a victim of cybercrime. The data shows that victims are reluctant to approach the authorities to report cybercrime as they are uncertain who to report to. Those that experienced financial crime approached their bank but others, who experienced other forms of cybercrime, were afraid that they would not be taken seriously by the authorities. Furthermore, it became evident that participants were not aware that South Africa has legislation, namely the Cybercrimes Act 19 of 2020, in place to provide for the prosecution of cybercrime. Where participants were aware of the legislation, it was predominantly as a result of being informed about it at their educational institutions. The study concludes that cybervictims have a lack of confidence in the authorities ability to deal with cybercrimes and do not feel the current legislative framework in place in South Africa is sufficient to address the issue of cybercrime.